Role of subxiphoid uniportal video-assisted thoracoscopic surgery in pulmonary metastasectomy - Elkhayat, Hussein; Hamza, Hesham; Elshoieby, Mahmoud; Omar, Mohamed; Gaber, Ebrahim (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2022)
Optimal management for patients with pulmonary metastasis is still debated. True survival benefit from widely practiced pulmonary metastasectomy (PM) is yet to be proved from high-quality randomized controlled trials. The ideal surgical approach for PM is also not generally agreed. VATS offers enhanced recovery and superior functional outcomes but at the expense of less detection of lung nodules and higher possibility of narrow/positive resection margins. The subxiphoid uniportal VATS (uVATS) approach is an evolving new approach with potential advantages including simultaneous access to both lung fields, less pain and faster rehabilitation. These advantages make it a favorable approach for PM, particularly in the setting of bilateral metastases. However, its use is still limited to case reports of a small number of patients. There is room for improvements in subxiphoid uVATS due to reported technical challenges and limitations. Herein, we aim to publicize a comprehensive review of literature on applications of subxiphoid uVATS in PM.